Karakteristik Kimia dan Organoleptik Permen Susu Sapi dengan Penambahan Madu dan Tepung Temulawak - Matilde Maria Alves; Gomera Bouk; Ning Ayu Dwi Tiya (Jurnal Multidisiplin Indonesia, 2026)
This study aimed to determine the effect of honey and curcuma flour addition on the chemical and organoleptic characteristics of cow’s milk candy. The method used was descriptive quantitative data analysis. The parameters observed included crude protein content, crude fat content, moisture content, and organoleptic tests for color, aroma, texture, and taste. The chemical analysis results showed that crude protein content increased from 3.166% in P0 to 3.818% in P3 as the proportion of honey and curcuma flour increased, while crude fat content decreased from 4.223% in P0 to 3.532% in P3. The moisture content of the candy was low, ranging from 2.464% to 3.173% with an average dry matter of 97.18%. The organoleptic test results showed that P0 was the most preferred by panelists for color, aroma, and taste, while P3 was the most preferred for texture due to its firmer and non-sticky consistency. It can be concluded that the addition of honey and curcuma flour can increase the nutritional value of milk candy in terms of protein and produce a lower-fat product without losing the basic characteristics of milk candy.